Polyphase polygonal serpentine veins in the Rocciavrè meta-ophiolite (Western Alps, NW Italy) - Luca Barale; Giancarlo Capitani; Roberto Compagnoni; Roberto Conconi; Roberto Cossio; Linda Pastero; Marcello Mellini (Lithos, 2025)

Structured Demographic Buffering: A Framework to Explore the Environmental Components and Demographic Mechanisms Underlying Demographic Buffering - Samuel J. L. Gascoigne; Maja Kajin; Shripad Tuljapurkar; Gabriel Silva Santos; Aldo Compagnoni; Ulrich K. Steiner; Anna C. Vinton; Harman Jaggi; Irem Sepil; Roberto Salguero‐Gómez (Ecology Letters, 2025)
Environmental stochasticity is a key determinant of population viability. Decades of work exploring how environmental stochasticity influences population dynamics have highlighted the ability of some natural populations to limit the negative effects of environmental stochasticity, one of the strategies being demographic buffering. Whilst various methods exist to quantify demographic buffering, we still do not know which environmental components and demographic mechanisms are most responsible for the demographic buffering observed in natural populations. Here, we introduce a framework to explore the relative impacts of environmental components (i.e., temporal autocorrelation and variance in demographic rates) on demographic buffering and the demographic mechanisms that underly these impacts (i.e., population structure and demographic rates). Using integral projection models, we show how demographic buffering is more sensitive to environmental variance relative to environmental autocorrelation. In addition, environmental autocorrelation and variance impact demographic buffering through distinct demographic mechanisms—i.e., population structure and demographic rates, respectively.

Unusual spinel in the “Verde Prato” serpentinized peridotite - Giancarlo Capitani; Roberto Compagnoni; Roberto Cossio; Linda Pastero; Roberto Conconi; Marcello Mellini (Lithos, 2024)

Demographic synthesis for global tree species conservation - Bettina Ohse; Aldo Compagnoni; Caroline E. Farrior; Sean M. McMahon; Roberto Salguero-Gómez; Nadja Rüger; Tiffany M. Knight (Trends in Ecology & Evolution, 2023)

Phenotypic plasticity masks range‐wide genetic differentiation for vegetative but not reproductive traits in a short‐lived plant - Jesus Villellas; Johan Ehrlén; Elizabeth E. Crone; Anna Mária Csergő; Maria B. Garcia; Anna‐Liisa Laine; Deborah A. Roach; Roberto Salguero‐Gómez; Glenda M. Wardle; Dylan Z. Childs; Bret D. Elderd; Alain Finn; et al. (Ecology Letters, 2021)
Genetic differentiation and phenotypic plasticity jointly shape intraspecific trait variation, but their roles differ among traits. In short‐lived plants, reproductive traits may be more genetically determined due to their impact on fitness, whereas vegetative traits may show higher plasticity to buffer short‐term perturbations. Combining a multi‐treatment greenhouse experiment with observational field data throughout the range of a widespread short‐lived herb, Plantago lanceolata , we (1) disentangled genetic and plastic responses of functional traits to a set of environmental drivers and (2) assessed how genetic differentiation and plasticity shape observational trait–environment relationships. Reproductive traits showed distinct genetic differentiation that largely determined observational patterns, but only when correcting traits for differences in biomass. Vegetative traits showed higher plasticity and opposite genetic and plastic responses, masking the genetic component underlying field‐observed trait variation. Our study suggests that genetic differentiation may be inferred from observational data only for the traits most closely related to fitness.

Lagged and dormant season climate better predict plant vital rates than climate during the growing season - Sanne M. Evers; Tiffany M. Knight; David W. Inouye; Tom E. X. Miller; Roberto Salguero‐Gómez; Amy M. Iler; Aldo Compagnoni (Global Change Biology, 2021)
Understanding the effects of climate on the vital rates (e.g., survival, development, reproduction) and dynamics of natural populations is a long‐standing quest in ecology, with ever‐increasing relevance in the face of climate change. However, linking climate drivers to demographic processes requires identifying the appropriate time windows during which climate influences vital rates. Researchers often do not have access to the long‐term data required to test a large number of windows, and are thus forced to make a priori choices. In this study, we first synthesize the literature to assess current a priori choices employed in studies performed on 104 plant species that link climate drivers with demographic responses. Second, we use a sliding‐window approach to investigate which combination of climate drivers and temporal window have the best predictive ability for vital rates of four perennial plant species that each have over a decade of demographic data ( Helianthella quinquenervis , Frasera speciosa , Cylindriopuntia imbricata , and Cryptantha flava ). Our literature review shows that most studies consider time windows in only the year preceding the measurement of the vital rate(s) of interest, and focus on annual or growing season temporal scales. In contrast, our sliding‐window analysis shows that in only four out of 13 vital rates the selected climate drivers have time windows that align with, or are similar to, the growing season. For many vital rates, the best window lagged more than 1 year and up to 4 years before the measurement of the vital rate. Our results demonstrate that for the vital rates of these four species, climate drivers that are lagged or outside of the growing season are the norm. Our study suggests that considering climatic predictors that fall outside of the most recent growing season will improve our understanding of how climate affects population dynamics.

Extensive surface geophysical prospecting for seismic microzonation - Grazia Caielli; Roberto de Franco; Vincenzo Di Fiore; Dario Albarello; Stefano Catalano; Floriana Pergalani; Giuseppe Cavuoto; Michele Cercato; Massimo Compagnoni; Johann Facciorusso; Daniela Famiani; Fernando Ferri; et al. (Bulletin of Earthquake Engineering, 2020)

The Monviso Massif and the Cottian Alps as Symbols of the Alpine Chain and Geological Heritage in Piemonte, Italy - Franco Rolfo; Piera Benna; Paola Cadoppi; Daniele Castelli; Sergio E. Favero-Longo; Marco Giardino; Gianni Balestro; Elena Belluso; Alessandro Borghi; Fernando Cámara; Roberto Compagnoni; Simona Ferrando; et al. (Geoheritage, 2015)

Late-Alpine rodingitization in the Bellecombe meta-ophiolites (Aosta Valley, Italian Western Alps): evidence from mineral assemblages and serpentinization-derived H 2 -bearing brine - Simona Ferrando; Maria Luce Frezzotti; Paolo Orione; Riccardo Carlo Conte; Roberto Compagnoni (International Geology Review, 2010)

Jadeite with the Ca-Eskola molecule from an ultra-high pressure metagranodiorite, Dora-Maira Massif, Western Alps - Marco Bruno; Roberto Compagnoni; Takao Hirajima; Marco Rubbo (Contributions to Mineralogy and Petrology, 2002)

Thermodynamic analysis of garnet growth zoning in eclogite facies granodiorite from M. Mucrone, Sesia Zone, Western Italian Alps - Rubbo Marco; Borghi Alessandro; Compagnoni Roberto (Contributions to Mineralogy and Petrology, 1999)

Metamorphic veins with kyanite, zoisite and quartz in the Zhu‐Jia‐Chong eclogite, Dabie Shan, China - Daniele Castelli; Franco Rolfo; Roberto Compagnoni; Shutong Xu (Island Arc, 1998)
The Zhu‐Jia‐Chong quartz eclogites occur within two mica–epidote–garnet–plagioclase gneiss as lenses up to 200 m thick and more than 1 km long. The eclogite is medium‐grained and consists of omphacite, garnet, clinozoisite, minor kyanite and quartz. No evidence for the former presence of coesite was found. Locally, poikiloblastic amphibole occurs, which is zoned from glaucophane in the core to Mg–cummingtonite in the rim. In some localities, clinozoisite occurs as polycrystalline aggregates, interpreted as pseudomorphs after former porphyroblasts of lawsonite. The eclogite is cut by irregular metamorphic veins up to 20 cm thick and several meters long, consisting of kyanite ± zoisite ± omphacite ± rutile ± apatite ± clinozoisite in a quartz matrix. Locally, vein minerals attain pegmatite‐like grain size. Geothermobarometric calculations and mineral compatibilities of peak and retrograde minerals of both eclogite and veins indicate a clockwise P–T path, characterized by initial eclogitic conditions prograding from the lawsonite to the epidote stability field. The veins are considered to have formed before peak metamorphic conditions by prograde dehydration of lawsonite to kyanite + zoisite/clinozoisite + quartz + fluid; the fluid released from the reaction favored the growth of coarse‐grained vein minerals. The eclogitic peak, estimated at ∼ 24 kbar and 700 °C, is followed by a two‐stage retrograde evolution: the earlier stage, characterized by a quasi‐adiabatic decompression from eclogite‐ to the amphibolite‐facies conditions, implies a rapid exhumation from depths of ∼ 90 km to mid‐crustal levels; the later stage, characterized by slower exhumation rates, led to the final exposure of eclogites and country rocks. The role of lawsonite as storage of fluid in subducting plates is therefore discussed.